Endovascular intervention for portal vein system thrombosis in a patient with protein S deficiency: A case report - Min Jeong Choi; Il Han Song (International Journal of Gastrointestinal Intervention)
Systemic anticoagulation is the first-line treatment for symptomatic portal vein system thrombosis (PVST). However, anticoagulation alone may be insufficient to prevent thrombus propagation, and failure to restore portal flow can lead to bowel infarction and portal hypertension. We report a case of successful endovascular intervention via a transhepatic portal vein approach to treat extensive PVST in a 73-year-old woman with a noncirrhotic liver. The thrombosis was attributed to protein S deficiency. Substantial recanalization of the portal venous system was achieved, and the patient has remained asymptomatic for five months post-procedure. This case highlights the challenges of managing extensive subacute PVST in the context of a prothrombotic condition and underscores the efficacy of a tailored endovascular approach.